Phthalocyanines : interaction with carbon structures and as PDT agents - Lourenço, Leandro Miguel de Oliveira (2014)
This dissertation describes the synthesis and characterization of different phthalocyanine (Pc) derivatives, as well as some porphyrins (Pors), for supramolecular interaction with different carbon nanostructures, to evaluate their potential application in electronic nanodevices. Likewise, it is also reported the preparation and biological evaluation of interesting phthalocyanine conjugates for cancer photodynamic therapy (PDT) and microorganisms photodynamic inactivation (PDI). The phthalonitrile precursors were prepared from commercial phthalonitriles by nucleophilic substitution of -NO2, -Cl, or -F groups, present in the phthalonitrile core, by thiol or pyridyl units. After the synthesis of these phthalonitriles, the corresponding Pcs were prepared by ciclotetramerization using a metallic salt as template at high temperatures. A second strategy involved the postfunctionalization of hexadecafluorophthalocyaninato zinc(II) through the adequate substituents of mercaptopyridine or cyclodextrin units on the macrocycle periphery. The different compounds were structurally characterized by diverse spectroscopic techniques, namely 1H, 13C and 19F nuclear magnetic resonance spectroscopies (attending the elemental composition of each structure); absorption and emission spectroscopy, and mass spectrometry. For the specific photophysical studies were also used electrochemical characterization, femtosecond and raman spectroscopy, transmission electron and atomic force microscopy. It was highlighted the noncovalent derivatisation of carbon nanostructures, mainly single wall carbon nanotubes (SWNT) and graphene nanosheets with the prepared Pc conjugates to study the photophysical properties of these supramolecular nanoassemblies. Also, from pyridyl-Pors and ruthenium phthalocyanines (RuPcs) were performed Por-RuPcs arrays via coordination chemistry. The results obtained of the novel supramolecular assemblies showed interesting electron donor-acceptor interactions and might be considered attractive candidates for nanotechnological devices. On the other hand, the amphiphilic phthalocyanine-cyclodextrin (Pc-CD) conjugates were tested in biological trials to assess their ability to inhibit UMUC- 3 human bladder cancer cells. The results obtained demonstrated that these photoactive conjugates are highly phototoxic against human bladder cancer cells and could be applied as promising PDT drugs.